Open Access Journal Article Process Charges in the Felid of Medicine - Chia-Yu Lin (National Taiwan University, 2021)
As the number of open access (OA) journals gradually increases, their complex operation and high publication fees have attracted the attention of the academic community. This study explored the differences in article processing charge (APC) mechanism and price distribution of OA journals in the medical field. The research objects were journals in the medical field of the 2017 Journal Citation Reports (JCR) Science Citation Index Expanded. In total, 47 medical disciplines were analyzed. 2,665 journals were included after excluding duplicates included in related disciplines. Results showed that the proportion of journals with OA publishing for various medical disciplines was more than 70%. APC pricing in the medical field could be divided into six major methods, with most journals (79.95%) charging a fixed price. APCs varied greatly between journals, ranging from US$113 to US$6,000, journals charging US$3,000 were most (32.25%). Median APCs were highest (US$3,295) in the ALLERGY category. This study suggests that future expansion of research disciplines, explore the APC and pricing mechanisms in different fields, and find out the most favorable fee combination of the manuscript, hoping to have a more comprehensive understanding of APC operations. (Article content in Chinese with English extended abstract)